Fucosyllactose and L-fucose utilization of infant Bifidobacterium longum and Bifidobacterium kashiwanohense - Bunesova, Vera; Lacroix, Christophe; Schwab, Clarissa (BMC microbiology, 2016)
BACKGROUND: Human milk oligosaccharides (HMOs) are one of the major glycan source of the infant gut microbiota. The two species that predominate the infant bifidobacteria community, Bifidobacterium longum subsp. infantis and Bifidobacterium bifidum, possess an arsenal of enzymes including α-fucosidases, sialidases, and β-galactosidases to metabolise HMOs. Recently bifidobacteria were obtained from the stool of six month old Kenyan infants including species such as Bifidobacterium kashiwanohense, and Bifidobacterium pseudolongum that are not frequently isolated from infant stool. The aim of this study was to characterize HMOs utilization by these isolates. Strains were grown in presence of 2'-fucosyllactose (2'-FL), 3'-fucosyllactose (3'-FL), 3'-sialyl-lactose (3'-SL), 6'-sialyl-lactose (6'-SL), and Lacto-N-neotetraose (LNnT). We further investigated metabolites formed during L-fucose and fucosyllactose utilization, and aimed to identify genes and pathways involved through genome comparison. RESULTS: Bifidobacterium longum subsp. infantis isolates, Bifidobacterium longum subsp. suis BSM11-5 and B. kashiwanohense strains grew in the presence of 2'-FL and 3'- FL. All B. longum isolates utilized the L-fucose moiety, while B. kashiwanohense accumulated L-fucose in the supernatant. 1,2-propanediol (1,2-PD) was the major metabolite from L-fucose fermentation, and was formed in equimolar amounts by B. longum isolates. Alpha-fucosidases were detected in all strains that degraded fucosyllactose. B. longum subsp. infantis TPY11-2 harboured four α-fucosidases with 95-99 % similarity to the type strain. B. kashiwanohense DSM 21854 and PV20-2 possessed three and one α-fucosidase, respectively. The two α-fucosidases of B. longum subsp. suis were 78-80 % similar to B. longum subsp. infantis and were highly similar to B. kashiwanohense α-fucosidases (95-99 %). The genomes of B. longum strains that were capable of utilizing L-fucose harboured two gene regions that encoded enzymes predicted to metabolize L-fucose to L-lactaldehyde, the precursor of 1,2-PD, via non-phosphorylated intermediates. CONCLUSION: Here we observed that the ability to utilize fucosyllactose is a trait of various bifidobacteria species. For the first time, strains of B. longum subsp. infantis and an isolate of B. longum subsp. suis were shown to use L-fucose to form 1,2-PD. As 1,2-PD is a precursor for intestinal propionate formation, bifidobacterial L-fucose utilization may impact intestinal short chain fatty acid balance. A L-fucose utilization pathway for bifidobacteria is suggested.
Keywords: Feces; Propylene Glycol; sekvence nukleotidů; střeva; laktosa; Lactose; trisacharidy; Fatty Acids, Volatile; kyseliny sialové; RNA, Ribosomal, 16S; Infant; alfa-L-fukosidasa; Oligosaccharides; Milk, Human; Genome, Bacterial; Sialic Acids; fukosa; genom bakteriální; kyseliny mastné těkavé; DNA, Bacterial; DNA bakterií; lidé; oligosacharidy; propylenglykol; alpha-L-Fucosidase; Humans; Trisaccharides; metabolické sítě a dráhy; Bifidobacterium; kojenec; Fucose; RNA ribozomální 16S; Base Sequence; Bifidobacterium longum; mateřské mléko; Intestines; beta-Galactosidase; feces; Metabolic Networks and Pathways; beta-galaktosidasa